ACTR-35. A STUDY OF RACE AND SOCIOECONOMIC STATUS IMPACTING THERAPEUTIC CLINICAL TRIAL ENROLLMENT IN ADULT GLIOMAS PATIENTS. (11th November 2019) - Morshed, Ramin; Reihl, Sheantel; Kakaizada, Sofia; Zhang, Eric; Young, Jacob; Clarke, Jennifer; Butowski, Nicholas; Taylor, Jennie; Ann Oberheim-Bush, Nancy; Aghi, Manish; Berger, Mitchel; Chang, Susan; et al.
Abstract: OBJECT: Under-enrollment in clinical trials significantly limits valid analyses of clinical interventions and generalizability of findings. Often it results in premature study termination, with estimates of 22% to 50% of clinical trials terminated due to poor accrual. Currently, there are limited reports addressing the influence of race/ethnicity and socioeconomic status on clinical trial enrollment in patients with adult glioma. The goal of this study was to determine if these factors impact clinical trial participation for glioma patients. METHODS: 852 adult patients were identified from the UCSF Tumor Board Registry and analyzed to determine the rate of therapeutic clinical trial consideration, tumor board recommendation, and study enrollment based on clinical reports in their electronic medical records. RESULTS: At initial diagnosis, 30.7% and 18.0% of glioma patients were recommended and enrolled in a therapeutic clinical trial, respectively. At recurrence, 38.7% and 25.3% of patients were recommended and enrolled in a clinical trial, respectively. Nineteen percent of the study population belonged to a NIH-designated underrepresented minority group; Asian/Pacific-Islander comprising 10.3% overall. On univariate analysis, only in-state location, distance to the hospital, and WHO grade were associated with consideration, recommendation, and enrollment at initial diagnosis and recurrence. Minority status, insurance type, median household income, and percent below poverty were not associated with clinical trial recommendation or enrollment. CONCLUSION: Race and socioeconomic status did not impact clinical trial consideration, tumor board recommendation, or study enrollment. Our results do not support the premise that provider decisions are impacted by biases based on minority or socioeconomic status.